Evidence for the medicinal value of Squama Manitis (pangolin scale): A systematic review - Xinyao Jin; Hui Zi Chua; Keyi Wang; Nan Li; Wenke Zheng; Wentai Pang; Fengwen Yang; Bo Pang; Mingyan Zhang; Junhua Zhang (Integrative Medicine Research)
Background: Squama Manitis (pangolin scale) has been used in traditional Chinese medicine for thousands of years. However, its efficacy has not been systematically reviewed. This review aims to fill the gap. Methods: We searched six electronic databases including PubMed, Embase, Cochrane Library, China National Knowledge Infrastructure Database (CNKI), WanFang Database and SinoMed from inception to May 1, 2020. Search terms included “pangolin”, “Squama Manitis”, “Manis crassicaudata”, “Manis javanica”, “Malayan pangolins”, “Manis pentadactyla”, “Ling Li”, “Chuan Shan Jia”, “Shan Jia”, “Pao Jia Zhu”, “Jia Pian” and “Pao Shan Jia”. The Cochrane Risk of Bias (RoB) assessment tool and Newcastle-Ottawa Scale (NOS) were used to evaluate the risk of bias of the included randomized controlled trials (RCTs) and case control studies (CCSs). Results: After screening, 15 articles that met the inclusion criteria were finally included. There were 4 randomized controlled trials, 1 case control study, 3 case series and 7 case reports. A total of 15 different diseases were reported in these studies, thus the data could not be merged to generate powerful results. Two RCTs suggested that Squama Manitis combined with herbal decoction or antibiotics could bring additional benifit for treating postpartum hypogalactia and mesenteric lymphadenitis. However, this result was not reliable due to low methodological quality and irrational outcomes. The other two RCTs generated negative results. All the non-RCTs did not add any valuable evidence to the efficacy of Squama Manitis beacause of small samples, incomplete records, non-standardized outcome detection. In general, currently available evidence cannot support the clinical use of Squama Manitis. Conclusion: There is no reliable evidence that Squama Manitis has special medicinal value. The removal of Squama Manitis from Pharmacopoeia is rational.